Method for degrading polyphenyl ether plastic
By performing electrolysis treatment under mild conditions, polyphenylene ether, substituted pyrazole and ammonium electrolyte are mixed in a specific molar ratio, which solves the problem of polyphenylene ether plastic being difficult to degrade under mild conditions, achieves efficient degradation and transformation, and promotes Recycling of polyphenylene ether plastic.
Patent Information
- Application Number
- CN202411492049.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The prior art is difficult to efficiently degrade polyphenylene ether plastics under mild conditions, and traditional methods require high temperature and high pressure hydrogen.
By mixing polyzhenylene, replacing pyrazole, and electrolytic ammonium, electrolytic products are used under constant current to generate degradable products.
Under mild conditions (less than 100 ° C, no high -pressure hydrogen), high -efficiency degradation polyzene ether plastics are achieved, and high -value ketone degradation products are generated to promote the recycling and utilization of polyphenyl ether plastics.
Smart Images

Figure CN119352050A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic degradation, and in particular to a method for degrading polyphenylene ether plastics. Background Art
[0002] The chemical name of polyphenylene ether is poly 2,6-dimethyl-1,4-phenylene ether, and its chemical formula is C 30 H 22 O4, referred to as PPO (Polyphenylene Oxide) or PPE (Polypheylene ether), is a high-strength engineering plastic developed in the 1960s. It has an annual output of about 500,000 tons and is one of the world's top five general-purpose engineering plastics. [1] Polyphenylene ether has stable chemical properties, wear resistance, non-toxicity, and excellent comprehensive properties. Its greatest feature is that it has excellent dimensional stability and outstanding electrical insulation under long-term load, and a wide range of operating temperatures. Polyphenylene ether has excellent water resistance and steam resistance, and the finished product has high tensile strength and impact strength, and good creep resistance. In addition, it has good wear resistance and electrical properties. It is widely used in the fields of electronics, automobiles, machinery, chemicals, etc.
[0003] While polyphenylene ether brings many conveniences, there are great difficulties in the degradation of its waste. The main structural unit of polyphenylene ether is diaromatic ether, in which the carbon-oxygen bond is very stable, and its bond energy reaches 315kcal / mol. [2] Therefore, the chemical degradation of polyphenylene ether is very difficult. At present, there are only a few reports on the degradation of polyphenylene ether. For example, in 2021, Yan and Wang reported the use of Ru / Nb2O5 catalyst to degrade polyphenylene ether under high temperature (280 degrees Celsius) and high pressure hydrogen (5 bar) conditions to produce meta-xylene with a yield of 85%. [3] Despite the above reports, how to achieve high-value and efficient conversion of polyphenylene ether plastics under mild conditions (without high temperature and avoiding the use of high-pressure hydrogen) has become a scientific and technological problem that needs to be solved urgently by technicians in this field.
[0004] References:
[0005] [1]Acute Market Reports. "Global polyphenylene oxide (PPO) resins marketsize&share, application analysis, regional outlook, growth trends, key players, competitive strategies and forecasts to 2026", 2018.
[0006] [2]K.Lee,Y.Jing,Y.Wang,N.Yan,Nat.Rev.Chem.2022,6,635–652.
[0007] [3]Y.Jing,Y.Wang,S.Furukawa,J.Xia,C.Sun,MJHglsey,H.Wang,Y.Guo,X.Liu,N.Yan,Angew.Chem.Int.Ed.2021,60,5527–5535. Summary of the invention
[0008] The purpose of the present invention is to provide a method for degrading polyphenylene ether plastics under mild conditions, so as to achieve high-value recycling of polyphenylene ether plastics.
[0009] In order to achieve the above object, the technical solution of the present invention is as follows:
[0010] A method for degrading polyphenylene ether plastics comprises the following steps: mixing polyphenylene ether, substituted pyrazole and electrolyte ammonium in a molar ratio of 1:(4-6):(0.5-1.5), adding a solvent, and performing constant current electrolysis for 8-20 hours to obtain a degradation product; the structural formula of the substituted pyrazole is:
[0011]
[0012] Among them, R 1 , R 2 , R 3 Each is independently selected from: hydrogen and halogen.
[0013] In one preferred embodiment, the electrolyte is any one or more of tetrabutyl tetrafluoroboric acid, lithium trifluoromethanesulfonate, and tetrabutyl ammonium hexafluorophosphate.
[0014] Tetrabutyl tetrafluoroboric acid, lithium trifluoromethanesulfonate, and tetrabutylammonium hexafluorophosphate are electrolytes, which play a role in enhancing conductivity. In the present invention, although a similar electrolyte, tetrabutylammonium acetate, can also play a role in enhancing conductivity, no product is obtained.
[0015] If the amount of substituted pyrazole and electrolyte ammonium is too small, the degradation process is incomplete and the yield is low; if the amount of substituted pyrazole and electrolyte ammonium is too large, there are too many impurities in the degradation product.
[0016] In one preferred embodiment, R 1 , R 3 is hydrogen, R 2 is hydrogen or halogen.
[0017] In one preferred embodiment, R 1 , R3 is hydrogen, R 2 It is a halogen.
[0018] In one preferred embodiment, R 1 , R 3 is hydrogen, R 2 is chlorine or fluorine.
[0019] In a preferred embodiment, the solvent is a mixed solution of toluene and acetonitrile.
[0020] In one preferred embodiment, the volume ratio of toluene to acetonitrile is 2-5:1.
[0021] In one preferred embodiment, the reaction temperature of the constant current electrolysis is 60-100°C.
[0022] In one preferred embodiment, the reaction temperature of the constant current electrolysis is 80-90°C.
[0023] In one preferred embodiment, the anode of the constant current electrolysis is a graphite rod or graphite paper.
[0024] In one preferred embodiment, the diameter of the graphite rod is 4-8 mm.
[0025] In one preferred embodiment, the length, width and height of the graphite paper are 1-3 cm, 1-2 cm and 0.03-0.07 cm respectively.
[0026] In one preferred embodiment, the cathode of the constant current electrolysis is a platinum sheet or graphite paper.
[0027] In one preferred embodiment, the current of constant current electrolysis is 3-10 mA.
[0028] In one preferred embodiment, the current of constant current electrolysis is 3-7 mA.
[0029] In one preferred embodiment, the constant current electrolysis time is 12-15 hours.
[0030] The degradation route of the degradable polyphenylene ether plastic is:
[0031]
[0032] The degradation products were quantified using hydrogen spectrum of nuclear magnetic spectrometer with dibromomethane added as internal standard for quantitative analysis.
[0033] The present invention utilizes an electrochemical method to realize a reaction route of polyphenylene ether plastic degradation products under mild conditions (below 100° C., without the need for hydrogen), converting polyphenylene ether plastic into high-value degradation product ketone compounds, thereby realizing the recycling of polyphenylene ether plastics, and providing a new path for the degradation and conversion of polyphenylene ether plastics. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The degradation test device of polyaniline, (1) is the anode and cathode used in the experiment; (2) is the test tube used for the reaction; (3) is a schematic diagram of the electrodes in the reaction tube; (4) is a schematic diagram of the heating experiment. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field based on the present application belong to the scope of protection of the present application.
[0036] The present application has no particular restrictions on the types of magnetic stirrers and borosilicate glass test tubes, and those skilled in the art can choose according to actual conditions as long as the purpose of the present application can be achieved.
[0037] The present application has no particular limitation on the weight average molecular weight of the polyphenylene ether plastic, as long as the purpose of the present application can be achieved.
[0038] In the present application, yield refers to the ratio of the actual production output of the product obtained by inputting a unit amount of raw materials (ie polyester plastics) to the theoretically calculated product output.
[0039] The present application uses a nuclear magnetic resonance spectrometer and a mass spectrometer to perform qualitative and quantitative analysis on the reaction systems of various embodiments and comparative examples.
[0040] Example 1
[0041] use Figure 1 The device shown in the figure is used to perform a degradation test of polyaniline. In the figure, (1) is the anode and cathode used in the experiment; (2) is the test tube used for the reaction; (3) is a schematic diagram of the electrodes in the reaction tube; (4) is a schematic diagram of the heating experiment. The specific degradation test process is as follows:
[0042] Polyphenylene ether (25.0 mg, 0.2 mmol, weight average molecular weight of 50,000), 4-chloropyrazole (102.5 mg, 1.0 mmol), and tetrabutylammonium tetrafluoroborate (65.9 mg, 0.2 mmol) were added to a 10 ml dry borosilicate glass test tube equipped with a magnetic stirrer, wherein the molar ratio of the three reagents was 1:5:1. Subsequently, 2.0 ml of toluene and 1.0 ml of acetonitrile were added, and the solution was mixed evenly in a volume ratio of 2:1. The reaction system used a graphite rod (diameter of 6 mm) as an anode and a platinum sheet (length × width × thickness = 2 cm × 1 cm × 0.02 cm) as a cathode, and a constant current electrolysis method was used to obtain degradation products. The reaction temperature was 80°C, the current was 5 mA, and the reaction time was 14 hours. The product was quantitatively analyzed using a nuclear magnetic spectrometer hydrogen spectrum, and dibromomethane was added as an internal standard, and the yield of ketone degradation products was 54%.
[0043] The reaction equation is as follows:
[0044]
[0045] The characterization data of the product are as follows:
[0046] H NMR 1 H NMR (400MHz, CDCl3) δ7.58(s,2H),7.56(s,2H),7.29(s,2H),2.06(s,6H).
[0047] C NMR 13 C NMR (101MHz, CDCl3) δ184.7,139.6,137.8,134.9,126.0,111.7,72.8,16.1.
[0048] High Resolution Mass Spectrometry (ESI) HRMS for [C 14 H 12 Cl2N4O+H + ]calculated:323.0461,found:323.0464.
[0049] Example 2
[0050] The electrolyte was replaced by lithium trifluoromethanesulfonate (LiOTf) from tetrabutylammonium tetrafluoroborate, and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 37%.
[0051] Example 3
[0052] The electrolyte was replaced by tetrabutylammonium tetrafluoroborate with tetrabutylammonium acetate (nBu4OAc), and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 0%.
[0053] Example 4
[0054] The electrolyte was replaced by tetrabutylammonium tetrafluoroborate with tetrabutylammonium hexafluorophosphate (nBu4PF6), and the rest was the same as in Example 1. The yield of ketone degradation products was 48%.
[0055] Comparative Example 1
[0056] No electrolyte was added, and the rest was the same as in Example 1, and the yield of ketone degradation products obtained was 0%.
[0057] The test results of Examples 1-4 and Comparative Example 1 are shown in Table 1:
[0058] Table 1 Test results of Examples 1-4 and Comparative Example 1
[0059] Electrolytes Yield of degradation product ketone Example 1 Tetrabutylammonium tetrafluoroborate 54% Example 2 Lithium trifluoromethanesulfonate 37% Example 3 Tetrabutylammonium acetate 0% Example 4 Tetrabutylammonium hexafluorophosphate 48% Comparative Example 1 none 0%
[0060] Example 5
[0061] The equivalent molar ratio was changed from polyphenylene ether: substituted pyrazole: electrolyte = 1:5:1 to 1:4:1, and the rest was the same as in Example 1. The yield of ketone degradation products was 43%.
[0062] Example 6
[0063] The equivalent molar ratio was changed from polyphenylene ether: substituted pyrazole: electrolyte = 1:5:1 to 1:6:1, and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 52%.
[0064] Example 7
[0065] The equivalent molar ratio was changed from polyphenylene ether: substituted pyrazole: electrolyte = 1:5:1 to 1:5:0.5, and the rest was the same as in Example 1. The yield of ketone degradation products was 31%.
[0066] Example 8
[0067] The equivalent molar ratio was changed from polyphenylene ether: substituted pyrazole: electrolyte = 1:5:1 to 1:5:1.5, and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 51%.
[0068] Example 9
[0069] The equivalent molar ratio was changed from polyphenylene ether: substituted pyrazole: electrolyte = 1:5:1 to 1:5:2, and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 52%.
[0070] The test results of Examples 1, 5-9 are shown in Table 2:
[0071] Table 2 Test results of Examples 1, 5-9
[0072]
[0073]
[0074] Example 10
[0075] The reaction time was adjusted from 14 hours to 8 hours, and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 6%.
[0076] Embodiment 11
[0077] The reaction time was adjusted from 14 hours to 12 hours, and the rest was the same as in Example 1. The yield of ketone degradation products was 25%.
[0078] Example 12
[0079] The reaction time was adjusted from 14 hours to 20 hours, and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 20%.
[0080] The test results of Examples 1, 10-12 are shown in Table 3:
[0081] Table 3 Test results of Examples 1, 10-12
[0082] Reaction time / h Yield of degradation product ketone Example 1 14 54% Example 10 8 6% Embodiment 11 12 25% Example 12 20 20%
[0083] In Example 10, a new by-product was observed. This by-product may be an intermediate. The intermediate reacted with pyrazole again to generate ketone. It may be that the reaction time was short and the intermediate did not have time to convert.
[0084] The reaction scheme of Example 10 is as follows:
[0085]
[0086] Example 13
[0087] The reaction current was adjusted from 5 mA to 3 mA, and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 29%.
[0088] Embodiment 14
[0089] The reaction current was adjusted from 5 mA to 7 mA, and the rest was the same as in Example 1. The yield of ketone degradation products was 34%.
[0090] Embodiment 15
[0091] The reaction current was adjusted from 5 mA to 10 mA, and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 16%.
[0092] Comparative Example 2
[0093] The reaction current was adjusted from 5 mA to 0 mA, and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 0%.
[0094] The test results of Examples 1, 13-15 and Comparative Example 2 are shown in Table 4:
[0095] Table 4 Test results of Examples 1, 10-12 and Comparative Example 2
[0096] Reaction current / mA Yield of degradation product ketone Example 1 5 54% Example 13 3 29% Embodiment 14 7 34% Embodiment 15 10 16% Comparative Example 1 0 0%
[0097] Example 16
[0098] The reaction temperature was adjusted from 80° C. to 60° C., and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 7%.
[0099] Embodiment 17
[0100] The reaction temperature was adjusted from 80° C. to 70° C., and the rest was the same as in Example 1. The yield of ketone degradation products was 20%.
[0101] Embodiment 18
[0102] The reaction temperature was adjusted from 80° C. to 90° C., and the rest was the same as in Example 1. The yield of ketone degradation products was 43%.
[0103] The test results of Examples 1 and 16-18 are shown in Table 5:
[0104] Table 5 Test results of Examples 1 and 16-18
[0105] Reaction temperature / ℃ Yield of degradation product ketone Example 1 80 54% Example 13 60 7% Embodiment 14 70 20% Embodiment 15 90 43%
[0106] Embodiment 19
[0107] The electrode anode was adjusted from graphite rod (diameter 6 mm) to graphite paper (length×width×thickness=2 cm×1 cm×0.05 cm), and the rest was the same as Example 1. The yield of ketone degradation products obtained was 26%.
[0108] Embodiment 20
[0109] The electrode anode was changed from a graphite rod (6 mm in diameter) to a platinum sheet (length×width×thickness=2 cm×1 cm×0.02 cm), and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 31%.
[0110] Embodiment 21
[0111] The solvent was adjusted from toluene:acetonitrile (volume ratio 2:1) to 100% toluene, and the rest was the same as in Example 1, and the yield of ketone degradation products obtained was 0%.
[0112] Embodiment 22
[0113] The solvent was adjusted from toluene:acetonitrile (volume ratio 2:1) to toluene:acetonitrile (volume ratio 5:1), and the rest was the same as in Example 1. The yield of ketone degradation products was 30%.
[0114] Embodiment 23
[0115] The solvent was adjusted from toluene:acetonitrile (volume ratio 2:1) to toluene:acetonitrile (volume ratio 1:1), and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 10%.
[0116] Embodiment 24
[0117] The solvent was adjusted from toluene:acetonitrile (volume ratio 2:1) to toluene:acetonitrile (volume ratio 1:2), and the rest was the same as in Example 1. The yield of ketone degradation products obtained was 6%.
[0118] Embodiment 25
[0119] The solvent was adjusted from toluene:acetonitrile (volume ratio 2:1) to 100% acetonitrile, and the rest was the same as in Example 1, and the yield of ketone degradation products obtained was 0%.
[0120] The test results of Examples 1, 21-25 are shown in Table 6:
[0121] Table 6 Test results of Examples 1, 21-25
[0122]
[0123]
[0124] Embodiment 26
[0125] The reaction reagent 4-chloropyrazole was replaced with pyrazole, and the rest was the same as in Example 1. The reaction route was shown below, and the yield of degradation product ketones was 5%.
[0126]
[0127] Embodiment 27
[0128] The reaction reagent 4-chloropyrazole was adjusted to 4-fluoropyrazole, and the rest was the same as in Example 1. The reaction route was shown below, and the yield of the degradation product ketone was 10%.
[0129]
[0130] Embodiment 28
[0131] The reaction reagent 4-chloropyrazole was adjusted to 5-methylpyrazole, and the rest was the same as in Example 1. The reaction route was shown below, and the yield of the degradation product ketone was 0%.
[0132]
[0133] The test results of Examples 1, 26-28 are shown in Table 7:
[0134] Table 7 Test results of Examples 1, 26-28
[0135] Substituted pyrazoles Yield of degradation product ketone Example 1 4-Chloropyrazole 54% Embodiment 21 Pyrazole 5% Embodiment 22 4-Fluoropyrazole 10% Embodiment 23 5-Methylpyrazole 0%
[0136] The above is only an embodiment of the present invention, and the common sense such as the known specific structure and characteristics in the scheme is not described in detail here. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the attached claims rather than the above description, so it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any figure mark in the claims should not be regarded as limiting the claims involved.
Claims
1. A method for degrading polyphenylene ether plastics, characterized in that: The following steps are involved: After mixing polyphenylene ether, substituted pyrazole and electrolyte in a molar ratio of 1:(4-6):(0.5-1.5), adding solvent, and performing constant current electrolysis for 8-20 hours to obtain a degradation product; the structural formula of the substituted pyrazole is: Among them, R 1 , R 2 , R 3 Each is independently selected from: hydrogen and halogen.
2. The method for degrading polyphenylene ether plastics according to claim 1, characterized in that: The electrolyte is any one or more of tetrabutyl tetrafluoroboric acid, lithium trifluoromethanesulfonate, and tetrabutyl ammonium hexafluorophosphate.
3. The method for degrading polyphenylene ether plastics according to claim 1, characterized in that: R 1 , R 3 is hydrogen, R 2 is hydrogen or halogen.
4. The method for degrading polyphenylene ether plastics according to claim 1, characterized in that: The solvent is a mixed solution of toluene and acetonitrile.
5. The method for degrading polyphenylene ether plastics according to claim 3, characterized in that: The volume ratio of toluene to acetonitrile is 2-5:
1.
6. The method for degrading polyphenylene ether plastics according to claim 1, characterized in that: The reaction temperature of constant current electrolysis is 60-100°C.
7. The method for degrading polyphenylene ether plastics according to claim 1, characterized in that: The anode for constant current electrolysis is a graphite rod or graphite paper.
8. The method for degrading polyphenylene ether plastics according to claim 1, characterized in that: The cathode of constant current electrolysis is platinum sheet or graphite paper.
9. The method for degrading polyphenylene ether plastics according to claim 1, characterized in that: The constant current electrolysis time is 12-15h.
10. The method for degrading polyphenylene ether plastics according to any one of claims 1 to 9, characterized in that: The current for constant current electrolysis is 3-10 mA.
Citation Information
Patent Citations
Method for degrading plastic
CN116693933A
Degradation method of polyalcohol acid ester plastic
CN117126054A
Polyester plastic degradation method
CN117185901A
Method for depolymerizing lignin through electrocatalysis and application
CN117737754A
Degradation method of polylactic acid plastic
CN118005511A